2013
DOI: 10.1093/geront/gns165
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Individual and Contextual Characteristics on the Provision of Individualized Care in Long-Term Care Facilities

Abstract: These findings suggest that both contextual- and individual-level factors exert considerably less influence on I-Care than factors associated to staffs' perceptions of empowerment. Consequently, interventions aimed at increasing I-Care in LTC settings should carefully consider staffs' access to structural empowerment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 27 publications
1
31
1
2
Order By: Relevance
“…Reflecting on the question of what had contributed to the improvement of daily activities and the development of cultural values associated with person-centred care, this research largely confirms that of earlier research [6,9,13,14,51]. The promotion of dialogue, participation and influence of the staff during every phase of the project, joint decision-making and continuous appreciative and adaptive facilitation all contributed to transformational change.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Reflecting on the question of what had contributed to the improvement of daily activities and the development of cultural values associated with person-centred care, this research largely confirms that of earlier research [6,9,13,14,51]. The promotion of dialogue, participation and influence of the staff during every phase of the project, joint decision-making and continuous appreciative and adaptive facilitation all contributed to transformational change.…”
Section: Discussionsupporting
confidence: 79%
“…She indicates that deep culture change is rare and that the adoption of culture change and person-centred practices remains inadequate, although the awareness of the culture change movement has grown in recent years. The main challenges to fundamental change seem to be staff motivation and vision, relationships between staff, residents and family, team work, and empowerment of staff [9,13,53,64]. Such challenges could be met by developing new shared cultural values, deep beliefs and patterns of unconscious basic assumptions [8,13,37,52,64].…”
Section: Introductionmentioning
confidence: 99%
“…To date, when attempting to advance our knowledge regarding meaningful improvements to the provision of care delivery in LTC settings, the role of culture remains vague, with the primary focus being on contextual-level (i.e., facility) characteristics [30]. The NCAT was conceptualized as six dimensions that were proposed to capture the unique nursing ethos within each setting that drives care delivery beliefs, values, and practice norms, as presented in Fig.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Managerial support was also highlighted as important for the delivery of interventions in care home settings in a successful intervention in Australia 210 and in an implementation study of the FITS care home intervention in the UK. 84 Staff perceptions of empowerment within their work environment can exert considerable influence on the delivery of individualised care, 172 which is also a prerequisite for case-specific intervention in dementia and CB. Disappointingly in our case studies, we found examples of managers who were unable to value their 'staff champions' by providing encouragement to use the resources, such as the technology and training opportunities we provided.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to delivery of the intervention to reduce antipsychotics in the FITS implementation study included unclear communication across management levels and values and ethos that contradicted the intervention approach. 84 Other studies have noted that staff perceptions of empowerment are important in the provision of individualised care; 172 values and beliefs that guide behaviour in an organisation can have an impact on depressive symptoms in nursing home residents; 173 and the impact of training initiatives on staff confidence and standards of care is often dependent on strong leadership and the home culture. 174 We will now consider our findings in the context of fidelity and adherence to the intervention.…”
Section: Limitations and Implications For Researchmentioning
confidence: 99%